A nano silver high thermal conductivity conductive adhesive for chip and preparation method thereof
By using silver powder composed of nano silver powder and micro silver powder in chip packaging, combined with epoxy resin and other additives, a tight stacking structure is formed, which solves the problem of insufficient thermal conductivity, electrical conductivity and adhesive properties of conductive glue, and achieves efficient improvements in thermal conductivity, conductivity and adhesive properties.
Patent Information
- Application Number
- CN202410794385.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-06-19
AI Technical Summary
The existing conductive adhesives have low thermal conductivity and electrical conductivity in chip packaging, insufficient adhesive performance, and low long-term stability and reliability.
The silver powder composed of nano silver powder and micro silver powder is combined with epoxy resin, tackifier and curing agent. By pretreating the silver powder to improve its dispersion and contact area, a tight stacking structure is formed to improve thermal conductivity, electrical conductivity and adhesive properties.
It significantly improves the thermal conductivity, conductivity and bonding properties of nano-silver high-thermal conductivity adhesives, and is suitable for high-temperature and high-precision chip packaging, improving the stability and reliability of temperature resistance bonding.
Smart Images

Figure BDA0004901027650000051 
Figure BDA0004901027650000061 
Figure BDA0004901027650000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of chip packaging materials, and more specifically, to a nano silver high thermal and electrical conductive adhesive applied to chips and a preparation method thereof. Background Art
[0002] Conductive adhesive is usually composed of resin matrix, conductive filler and additives. The commonly used resin matrix is epoxy resin, the conductive filler is silver powder, copper powder, aluminum powder, carbon black, etc., and the additives include curing agent, etc. As a new type of electronic environmentally friendly material, conductive adhesive is gradually replacing tin-lead solder and is widely used in chip packaging.
[0003] When conductive adhesive is used in chip packaging, due to the characteristics of chip integration and miniaturization, higher requirements are placed on the thermal conductivity and bonding performance of the conductive adhesive. At present, the thermal conductivity of the commonly used conductive adhesive is 5-10W / m·K. When used in some high-power and high-precision chip packaging, its applicability is relatively low.
[0004] At present, in order to improve the thermal conductivity and electrical conductivity of conductive adhesives, conductive adhesives are generally prepared by increasing the amount of conductive fillers and thermal conductive fillers. However, the addition of conductive fillers and thermal conductive fillers reduces the bonding performance of the conductive adhesives. When the chip is used under long-term high-heat conditions, the stability and reliability are reduced. Summary of the invention
[0005] In order to solve the problems of low thermal conductivity and electrical conductivity, low adhesion performance, low long-term stability and reliability of existing conductive adhesives when used in chip packaging, the present application provides a nano silver high thermal conductivity conductive adhesive for chips and a preparation method thereof.
[0006] In the first aspect, the present application provides a nano silver high thermal conductivity conductive adhesive for chips, which adopts the following technical solution:
[0007] A nano silver high thermal conductivity conductive adhesive for chips is prepared from the following raw materials in percentage by weight:
[0008] Silver powder 70-90%
[0009] Epoxy resin 3-15%
[0010] Tackifier 3-5%
[0011] Curing agent 2-4%
[0012] Solvent residue;
[0013] The silver powder consists of nano silver powder and micron silver powder. The particle size of the nano silver powder is 25-50 nm, and the particle size of the micron silver powder is 1-3 μm.
[0014] By adopting the above technical scheme, the present application uses epoxy resin as a bonding matrix, and adds a high proportion of silver powder to the epoxy resin, wherein the silver powder is composed of nano silver powder and micron silver powder, and the nano silver powder can be filled in the particle gaps of the micron silver powder to form a compact stacking structure with the micron silver powder, thereby increasing the contact area between the silver powder particles, thereby improving the thermal conductivity and electrical conductivity of the prepared nano silver high thermal conductivity conductive adhesive, and the compact stacking structure can also improve the molecular cohesion of the prepared nano silver high thermal conductivity conductive adhesive, thereby improving the bonding performance; the solvent can improve the fluidity and viscosity of the epoxy resin; under the action of the curing agent, the tackifier and the epoxy resin are cross-linked and cured, so that the silver powder is evenly dispersed in the epoxy resin system, and the prepared nano silver high thermal conductivity conductive adhesive has good thermal conductivity, electrical conductivity and bonding performance, is suitable for chip packaging, and has good temperature-resistant bonding stability and reliability.
[0015] In some preferred embodiments of the present application, the particle size of the nano silver powder may be 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm; the particle size of the micron silver powder may be 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.
[0016] Preferably, the weight ratio of the nano silver powder to the micron silver powder is (6-7):(1-2).
[0017] By adopting the above technical solution, nano silver powder and micron silver powder with an optimal weight ratio can form a densely packed filling structure, thereby improving the thermal conductivity, electrical conductivity and adhesion of the prepared nano silver high thermal conductive adhesive.
[0018] Preferably, the silver powder is pretreated silver powder, and the pretreated silver powder is prepared from the following raw materials in parts by weight:
[0019] Silver powder 80-100 parts
[0020] 50-85wt% ethanol aqueous solution 50-80 parts
[0021] Silane coupling agent 3-8 parts
[0022] Sodium percarbonate 0.5-1 part
[0023] 1-3 parts turpentine
[0024] Triallyl isocyanurate 3-5 parts
[0025] 2-4 parts of vinyl dimethyl terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer.
[0026] By adopting the above technical scheme, sodium percarbonate has a good activation effect on the surface of the silver powder, so that the surface of the silver powder is enriched with more hydroxyl groups, which is conducive to the grafting reaction between the silane coupling agent and the silver powder. Turpentine has good penetration and stretching effects, and can fully disperse the silver powder modified by the silane coupling agent, thereby improving the dispersion of the silver powder in the dimethyl-methyltrifluoropropyl polysiloxane copolymer terminated with triallyl isocyanurate and vinyl dimethyl, and improving the bonding between the silver powder and the dimethyl-methyltrifluoropropyl polysiloxane copolymer terminated with triallyl isocyanurate and vinyl dimethyl. The contact area of the methyl trifluoropropyl polysiloxane copolymer, the dimethyl-methyl trifluoropropyl polysiloxane copolymer terminated with triallyl isocyanurate and vinyl dimethyl produces a good synergistic effect, can be evenly dispersed and coated on the surface of the silver powder, and form a soft and uniform coating on the surface of the silver powder, thereby improving the dispersion of the silver powder in the epoxy resin system. The pretreated silver powder prepared in this way can be further cross-linked with the epoxy resin, which can improve the thermal conductivity and electrical conductivity of the prepared nano silver high thermal conductive conductive adhesive while also improving the bonding performance.
[0027] Preferably, the silane coupling agent is one or a combination of vinyl silane coupling agent, amino silane coupling agent, epoxy silane coupling agent, and methacryloxy silane.
[0028] By adopting the above technical solution, the above silane coupling agent and silver powder have a good grafting modification effect.
[0029] Preferably, the pretreated silver powder is prepared by the following steps:
[0030] A1. Add sodium percarbonate and silane coupling agent to 50-85wt% ethanol aqueous solution, stir to dissolve, then add silver powder, heat to 55-65°C, stir to react for 20-40min, filter, and obtain silane-grafted silver powder;
[0031] A2. Add turpentine, triallyl isocyanurate and vinyl dimethyl-terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer to the silane-grafted silver powder, raise the temperature to 80-90° C., knead and stir for 40-60 minutes to obtain pretreated silver powder.
[0032] By adopting the above technical scheme, silver powder is added to an ethanol aqueous solution containing sodium carbonate and a silane coupling agent, the silver powder is activated by sodium carbonate so that the surface of the silver powder is hydroxylated, and then the silane coupling agent is coupled and grafted with the surface hydroxylated silver powder under a relatively optimal temperature condition to prepare the silane-grafted silver powder; then turpentine, triallyl isocyanurate and a vinyl dimethyl-terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer are added to the silane-grafted silver powder, the turpentine is infiltrated and dispersed into the silane-grafted silver powder, so that the silane-grafted silver powder is fully dispersed, and the triallyl isocyanurate and the vinyl dimethyl-terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer form a uniform coating film on the surface of the silane-grafted silver powder, thereby preparing the pretreated silver powder.
[0033] Preferably, the epoxy resin is composed of bisphenol A epoxy resin and glycidyl ester epoxy resin in a weight ratio of (7-9):1.
[0034] By adopting the above technical scheme, bisphenol A epoxy resin and glycidyl ester epoxy resin are compounded with a better dosage ratio, which has better bonding stability to silver powder.
[0035] Preferably, the viscosity enhancer is composed of polymethyl vinyl ether / maleic anhydride copolymer and propoxyglycerol triglycidyl ether in a weight ratio of 1:(1-3).
[0036] By adopting the above technical scheme, the polymethyl vinyl ether / maleic anhydride copolymer has good adhesion and compatibility, and can produce a good synergistic effect with propoxyglycerol triglycidyl ether. The thickener composed of this composition can be further cross-linked with the epoxy resin to improve the dispersion uniformity of the silver powder in the epoxy resin system, thereby improving the thermal conductivity, conductivity and adhesion of the prepared nano silver high thermal conductivity conductive adhesive.
[0037] Preferably, the curing agent is at least one of aliphatic amine curing agents, polyamide curing agents, anhydride curing agents, and polyisocyanate curing agents.
[0038] By adopting the above technical solution, the above curing agent has good curing stability for epoxy resin, can make the epoxy resin system stably cured, and improve the comprehensive performance of the prepared nano silver high thermal conductivity and electrical conductive adhesive.
[0039] Preferably, the solvent is at least one of cyclohexanone, ethyl acetate, n-butyl acetate, isobutyl acetate and n-butanol.
[0040] By adopting the above technical solution, the above solvent has a good dilution effect on the epoxy resin and the tackifier, adjusts the viscosity of the system, and improves the processing stability.
[0041] In a second aspect, the present application provides a method for preparing a nano silver high thermal conductivity conductive adhesive for use in chips, using the following technical solution:
[0042] A method for preparing nano silver high thermal conductivity and electrically conductive adhesive for use in chips comprises the following steps:
[0043] S1. Add epoxy resin, tackifier and solvent into a mixing device and mix them evenly;
[0044] S2. Add silver powder and curing agent, mix well, and perform vacuum degassing to obtain nano silver high thermal conductivity and conductive adhesive for chips.
[0045] By adopting the above technical scheme, the epoxy resin and the tackifier are first evenly dispersed in the solvent, and then the silver powder and the curing agent are added and stirred evenly, and vacuum degassing is performed to eliminate the bubbles generated by the air, so as to obtain a nano silver high thermal conductivity and conductive adhesive for chips with a uniform dispersion system and stable performance.
[0046] In summary, this application has the following beneficial effects:
[0047] 1. The nano silver high thermal conductivity conductive adhesive used for chips of the present application is prepared by adding nano silver powder and micron silver powder with a relatively optimal particle size as silver powder into epoxy resin, and then compounding with a tackifier, a solvent and a curing agent. The nano silver high thermal conductivity conductive adhesive thus prepared has good thermal conductivity, electrical conductivity and bonding performance, is suitable for chip packaging, and has good temperature resistance bonding stability and reliability.
[0048] 2. The silver powder is surface pretreated by using sodium percarbonate, silane coupling agent, turpentine, triallyl isocyanurate and vinyl dimethyl-terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer. The pretreated silver powder obtained has good dispersibility and can be evenly dispersed in the epoxy resin system. It can also further undergo cross-linking reaction with the epoxy resin and the tackifier, thereby further improving the thermal conductivity, electrical conductivity and bonding properties of the obtained nano-silver high thermal conductive conductive adhesive.
[0049] 3. By using polymethyl vinyl ether / maleic anhydride copolymer and propoxyglycerol triglycidyl ether in a better dosage ratio as thickeners, it can further cure and cross-link with silver powder and epoxy resin during curing, further improving the dispersion and bonding performance of silver powder in the epoxy resin system, and further improving the thermal conductivity, electrical conductivity and adhesion of the prepared nano-silver high thermal conductivity conductive adhesive. DETAILED DESCRIPTION
[0050] The present application is further described in detail below with reference to the embodiments.
[0051] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used:
[0052] 1. Epoxy resin:
[0053] 1) Bisphenol A epoxy resin: Dow DER 383;
[0054] 2) Glycidyl ester epoxy resin: 4,5-epoxytetrahydrophthalic acid diglycidyl ester TDE-85, epoxy equivalent 117-120, viscosity 1600-2000mpa·s / 25℃;
[0055] 2. Turpentine: natural turpentine, CAS No. 8006-64-2, content greater than 99%;
[0056] 3. Triallyl isocyanurate: CAS No. 1025-15-6, content 98%;
[0057] 4. Vinyl dimethyl terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer: Nanjing SiSiB, SiSiB VF6960;
[0058] 5. Polymethyl vinyl ether / maleic anhydride copolymer: CAS No. 9011-16-9, molecular weight 13000-18000;
[0059] 6. Propoxyglycerol triglycidyl ether: CAS No. 37237-76-6, epoxy value 0.15-0.18eq / 100g.
[0060] Preparation Example of Pretreated Silver Powder
[0061] Preparation Example 1
[0062] Preparation Example 1 discloses a pretreated silver powder, which is prepared by the following steps:
[0063] A1. Add 0.05kg sodium percarbonate and 0.3kg KH560 as silane coupling agents to 50wt% ethanol aqueous solution, stir and dissolve, then add 8kg silver powder, the silver powder is composed of nano silver powder and micron silver powder in a weight ratio of 6:1, the particle size of the nano silver powder is 25nm, and the particle size of the micron silver powder is 1μm, heat to 55°C, stir and react for 20min, filter, and obtain silane-grafted silver powder; A2. Add 0.1kg turpentine, 0.5kg triallyl isocyanurate and 0.4kg vinyl dimethyl-terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer to the silane-grafted silver powder, heat to 80°C, knead and stir for 40min to obtain pretreated silver powder.
[0064] Preparation Example 2-3
[0065] The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.
[0066] Table 1 Raw material dosage and preparation conditions of Preparation Examples 1-3
[0067]
[0068]
[0069] Preparation Comparative Example 1
[0070] The difference between Preparation Comparative Example 1 and Preparation Example 1 is that the vinyl dimethyl terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer is replaced by triallyl isocyanurate in equal amounts, and the rest is the same as Preparation Example 1.
[0071] Preparation Comparative Example 2
[0072] The difference between Preparation Comparative Example 2 and Preparation Example 1 is that an equal amount of turpentine oil is replaced with a vinyl dimethyl-terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer, and the rest is the same as Preparation Example 1.
[0073] Preparation Comparative Example 3
[0074] The difference between Preparation Comparative Example 3 and Preparation Example 1 is that sodium percarbonate is not added, and the other steps are the same as Preparation Example 1.
[0075] Example
[0076] Example 1
[0077] Example 1 discloses a nano silver high thermal conductivity conductive adhesive for use in chips, which is prepared by the following steps:
[0078] S1, add 0.3kg bisphenol A epoxy resin, 0.4kg polyethylene glycol diglycidyl ether as a tackifier and 0.1kg ethyl acetate as a solvent into a mixer and mix well;
[0079] S2. Add 9kg of silver powder (the silver powder is composed of nano silver powder and micron silver powder in a weight ratio of 1:1, the particle size of the nano silver powder is 25nm, and the particle size of the micron silver powder is 1μm) and 0.2kg of diethylenetriamine and maleic anhydride in a weight ratio of 2:1 as a curing agent, mix well, and vacuum degas for 20 minutes at a vacuum degree of -0.08MPa to obtain nano silver high thermal conductivity and conductive adhesive for chip application.
[0080] Embodiment 2-4
[0081] The difference between Example 2-4 and Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 2 below for details.
[0082] Table 2 Raw material dosage and preparation conditions of Examples 1-4
[0083]
[0084]
[0085] Embodiment 5-10
[0086] The difference between Examples 5-10 and Example 2 is that the sources of the silver powder are different, and the silver powder is pretreated silver powder, as shown in Table 3 below.
[0087] Table 3 Sources of silver powder in Examples 5-10
[0088] Example Source of silver powder Example 5 Preparation Example 1 Example 6 Preparation Example 2 Example 7 Preparation Example 3 Example 8 Preparation Comparative Example 1 Example 9 Preparation Comparative Example 2 Example 10 Preparation Comparative Example 3
[0089] Embodiment 11
[0090] The difference between Example 11 and Example 5 is that the epoxy resin is different. The epoxy resin in Example 11 is composed of bisphenol A epoxy resin and glycidyl ester epoxy resin in a weight ratio of 7:1, and the rest is the same as Example 5.
[0091] Example 12
[0092] The difference between Example 12 and Example 11 is that the epoxy resin is composed of bisphenol A epoxy resin and glycidyl ester epoxy resin in a weight ratio of 9:1, and the rest is the same as Example 11.
[0093] Embodiment 13
[0094] The difference between Example 13 and Example 11 is that the thickener is different. The thickener in Example 13 is composed of polymethyl vinyl ether / maleic anhydride copolymer and propoxyglycerol triglycidyl ether in a weight ratio of 1:1, and the rest is the same as Example 11.
[0095] Embodiment 14
[0096] The difference between Example 14 and Example 13 is that the viscosity enhancer is composed of polymethyl vinyl ether / maleic anhydride copolymer and propoxyglycerol triglycidyl ether in a weight ratio of 1:3, and the rest is the same as Example 13.
[0097] Comparative Example
[0098] Comparative Example 1
[0099] The difference between Comparative Example 1 and Example 1 is that the particle size of the nano silver powder is 100 nm, and the particle size of the micron silver powder is 5 μm. The other aspects are the same as those of Example 1.
[0100] Comparative Example 2
[0101] The difference between Comparative Example 2 and Example 1 is that the micron silver powder is replaced by nano silver powder in equal amount, and the rest is the same as Example 1.
[0102] Comparative Example 3
[0103] The difference between Comparative Example 3 and Example 1 is that the tackifier is replaced by an epoxy resin in equal amount, and the rest is the same as Example 1.
[0104] Performance testing
[0105] The following is a performance test of the nano silver high thermal conductivity and conductive adhesive applied to chips prepared in Examples 1-14 and Comparative Examples 1-3:
[0106] (1) Thermal conductivity test:
[0107] According to the test method in ASTM D5470, the nano silver high thermal conductivity conductive adhesive was cured at a temperature of 80°C to form a test piece with a specification of 50mm*40mm*5mm, and the thermal conductivity coefficient (unit: W / m·K) was tested and the test results were recorded;
[0108] (2) Volume resistivity test:
[0109] Refer to the test method in ASTM D2739 to test the volume resistivity (unit: Ω·cm) of nano-silver high thermal conductivity conductive adhesive at 20°C, and test and record the test results;
[0110] (3) Adhesion performance test:
[0111] Refer to the test method in GB / T 7124-2008 to test the tensile shear strength (unit: MPa) of the nano-silver high thermal conductivity and conductive adhesive, and test and record the test results;
[0112] (4) High temperature bonding performance test:
[0113] Referring to the test method in GB / T 7124-2008, place the test sample in a constant temperature and humidity chamber at 85°C and 85% humidity. After 72 hours, test the tensile shear strength (unit: MPa) and record the test results.
[0114] The following are the performance test data of the nano silver high thermal conductivity and electrically conductive adhesive for chips of Examples 1-14 and Comparative Examples 1-3, see Table 4 below for details.
[0115] Table 4 Performance test data of nano silver high thermal conductivity conductive adhesive for chips of Examples 1-14 and Comparative Examples 1-3
[0116]
[0117]
[0118] Combining Examples 1-4 and Comparative Examples 1-2 and Table 4, it can be concluded that the use of the nano-silver powder and micron silver powder with a preferred particle size of the present application for compounding can improve the thermal conductivity, electrical conductivity and adhesion of the prepared nano-silver high thermal conductivity conductive adhesive, and the bonding performance is good under high temperature and high humidity conditions; in Comparative Example 1, the preferred particle size was not used for compounding, and the nano-silver powder was used alone in Comparative Example 2, and the thermal conductivity, electrical conductivity and adhesion of the prepared nano-silver high thermal conductivity conductive adhesive were all reduced. This may be because the nano-silver powder and micron silver powder with a preferred particle size can form a tightly structured thermal conductive channel and conductive channel with the epoxy resin, thereby improving the thermal conductivity and electrical conductivity of the nano-silver high thermal conductivity conductive adhesive, and the tightly structured system is also conducive to improving the bonding performance.
[0119] Combining Example 2 and Examples 5-10 and Table 4, it can be seen that the silver powder is further modified to obtain pretreated silver powder in the present application, which can further improve the thermal conductivity, conductivity and adhesion of the prepared nano silver high thermal conductivity conductive adhesive. In Examples 8-10, the silver powder is not pretreated using the pretreatment method of the present application, and the thermal conductivity, conductivity and adhesion of the prepared nano silver high thermal conductivity conductive adhesive are all reduced. This may be because the grafting efficiency of the silane coupling agent on the silver powder is reduced in the absence of the activation effect of sodium percarbonate, and the turpentine, triallyl isocyanurate and vinyl dimethyl-terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer are not used in combination, which reduces the synergistic effect of the three, thereby reducing the dispersion and adhesion of the prepared pretreated silver powder in the system.
[0120] Combining Example 5 and Examples 11-12 with Table 4, it can be concluded that compounding the bisphenol A epoxy resin and the glycidyl ester epoxy resin in the preferred dosage ratio of the present application can further enhance the bonding effect on the silver powder, thereby enhancing the thermal conductivity, electrical conductivity and adhesion of the prepared nano-silver high thermal conductive conductive adhesive.
[0121] Combining Example 11 and Examples 13-14, Comparative Example 3 and Table 4, it can be concluded that the use of the polymethyl vinyl ether / maleic anhydride copolymer and propoxyglycerol triglycidyl ether in the preferred dosage ratio of the present application as a tackifier can be further cured and cross-linked with the silver powder and the epoxy resin during curing, further improving the dispersion and bonding performance of the silver powder in the epoxy resin system, and further improving the thermal conductivity, electrical conductivity and adhesion of the prepared nano silver high thermal conductive conductive adhesive; in Comparative Example 3, the tackifier is replaced with epoxy resin, and the thermal conductivity and electrical conductivity of the prepared nano silver high thermal conductive conductive adhesive are slightly reduced, while the bonding performance and temperature resistance stability are significantly reduced, indicating that the tackifier of the present application has a good synergistic effect with the epoxy resin.
[0122] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A nano silver high thermal conductivity and conductive adhesive for use in chips, characterized in that: Made from the following raw materials in weight percentage: Silver powder 70-90% Epoxy resin 3-15% Thickener 3-5% Curing agent 2-4% Solvent residue; The silver powder is composed of nano silver powder and micron silver powder, the particle size of the nano silver powder is 25-50nm, and the particle size of the micron silver powder is 1-3µm; The silver powder is pretreated silver powder, and the pretreated silver powder is prepared from the following raw materials in parts by weight: Silver powder 80-100 parts 50-80 parts of 50-85wt% ethanol aqueous solution Silane coupling agent 3-8 parts Sodium percarbonate 0.5-1 part 1-3 parts turpentine Triallyl isocyanurate 3-5 parts 2-4 parts of vinyl dimethyl terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer; The pretreated silver powder is prepared by the following steps: A1. Add sodium percarbonate and silane coupling agent to 50-85wt% ethanol aqueous solution, stir to dissolve, then add silver powder, heat to 55-65°C, stir to react for 20-40min, filter, and obtain silane-grafted silver powder; A2, adding turpentine, triallyl isocyanurate and vinyl dimethyl terminated dimethyl-methyltrifluoropropyl polysiloxane copolymer to the silane-grafted silver powder, heating to 80-90° C., kneading and stirring for 40-60 minutes, to obtain pretreated silver powder; The viscosity enhancer is composed of polymethyl vinyl ether / maleic anhydride copolymer and propoxyglycerol triglycidyl ether in a weight ratio of 1:(1-3).
2. The nano silver high thermal and electrical conductive adhesive for chip according to claim 1, characterized in that: The weight ratio of the nano silver powder to the micron silver powder is (6-7): (1-2).
3. The nano silver high thermal and electrical conductive adhesive for chip according to claim 1, characterized in that: The silane coupling agent is one or a combination of vinyl silane coupling agent, amino silane coupling agent, epoxy silane coupling agent and methacryloxy silane.
4. The nano silver high thermal and electrical conductive adhesive for chips according to claim 1, characterized in that: The epoxy resin is composed of bisphenol A epoxy resin and glycidyl ester epoxy resin in a weight ratio of (7-9):
1.
5. The nano silver high thermal and electrical conductive adhesive for chip according to claim 1, characterized in that: The curing agent is at least one of aliphatic amine curing agents, polyamide curing agents, acid anhydride curing agents, and polyisocyanate curing agents.
6. The nano silver high thermal and electrical conductive adhesive for chips according to claim 1, characterized in that: The solvent is at least one of cyclohexanone, ethyl acetate, n-butyl acetate, isobutyl acetate and n-butanol.
7. A method for preparing a nano silver high thermal and electrical conductive adhesive for use in chips as claimed in any one of claims 1 to 6, characterized in that: The method comprises the following preparation steps: S1. Add epoxy resin, tackifier and solvent into a mixing device and mix them evenly; S2. Add silver powder and curing agent, mix well, and perform vacuum degassing to obtain nano silver high thermal conductivity and conductive adhesive for chips.
Citation Information
Patent Citations
Process for the continuous dyeing of threads and slivers of dry spun acrylonitrile polymers
CA1025156A
High thermal and electric conducting adhesive filled with nanometer silver and preparation method thereof
CN102311714A